2012
DOI: 10.1111/j.1743-6109.2011.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors Among Older Adults in Spain: Results from a Population-Based National Sexual Health Survey

Abstract: Introduction The Spanish National Sexual Health Survey (SNSHS) is designed to examine sexual activity, sexual behaviors, and sexual health among the Spanish population. Aim To describe sexual activity and behaviors of Spaniards aged ≥65 years old focusing on gender differences. Methods A population-based descriptive study was conducted using individual data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
1
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 28 publications
9
84
1
19
Order By: Relevance
“…Studies suggest that 40-65% of men and 25-55% of women in the 65-75 age group reported being sexually active in the past 12 months (Beckman et al, 2008;Field et al, 2013;Palacios-Ceña et al, 2012), with comparable proportions of aging women and men reporting that sexuality is important to them (Beckman et al, 2008). In the 1971-2001 repeated cross-sectional study of 70 year olds in a large Swedish city, the more recently surveyed participants were more sexually active, indicating a possible cultural change in how older individuals and couples perceive their sexuality (Beckman et al, 2008).…”
Section: Age-related Dynamics Of Sexual Satisfactionmentioning
confidence: 99%
“…Studies suggest that 40-65% of men and 25-55% of women in the 65-75 age group reported being sexually active in the past 12 months (Beckman et al, 2008;Field et al, 2013;Palacios-Ceña et al, 2012), with comparable proportions of aging women and men reporting that sexuality is important to them (Beckman et al, 2008). In the 1971-2001 repeated cross-sectional study of 70 year olds in a large Swedish city, the more recently surveyed participants were more sexually active, indicating a possible cultural change in how older individuals and couples perceive their sexuality (Beckman et al, 2008).…”
Section: Age-related Dynamics Of Sexual Satisfactionmentioning
confidence: 99%
“…Inostrane studije izveštavaju da stare osobe ostaju seksualno aktivne i tokom poslednjih decenija svog života (Herbenick et al, 2010;Huang et al, 2009), a da fizičko zdravlje značajno korelira sa mnogim aspektima seksualne aktivnosti, nezavisno od godina života (Lindau et al, 2007). Seksualna aktivnost je povezana sa činjenicama postojanja partnera i bolje samopercepcije zdravlja, dok su najčešći razlozi seksualne neaktivnosti nedovoljna zainteresovanost, smrt partnera ili fizička bolest (Palacios-Ceña et al, 2012). Indirektno povezana sa tom temom je tvrdnja iz primenjenog upitnika na koju je tačno odgovorio najmanji broj ispitanika (69 ili 24,6%), a odnosi se na činjenicu da su starije osobe sve više pod rizikom od HIV/ AIDS-a.…”
Section: Diskusijaunclassified
“…En este sentido, los estereotipos sobre la vejez atribuyen a esta etapa de la vida un declive o incluso una desaparición de los intereses y las necesidades sexuales 1 . Sin embargo, la investigación ha demostrado que no solo los mayores continúan manteniendo relaciones sexuales y teniendo interés por la sexualidad [2][3][4][5] , sino que este tipo de comportamientos e intereses promueve el mantenimiento de la salud y se relaciona con niveles más elevados de bienestar y satisfacción con la vida 6,7 .…”
Section: Introductionunclassified